Registration of ‘Clara CL’ wheat - Martin, Terry J.; Zhang, Guorong; Fritz, Allan K.; Miller, Rebecca; Chen, Ming-Shun (My University, 2014)
‘Clara CL’ (Reg. No. CV-XX; PI 665948) hard white winter wheat (Triticum aestivum L.) cultivar was developed at the Agricultural Research Center–Hays, Kansas State University and released by the Kansas Agricultural Experiment Station in 2011. Clara CL carries one Clearfield gene and has tolerance to imazamox herbicide. Clara CL was selected from a single cross of KS03HW154/KS03HW1 using a modified bulk breeding method. Both parental lines are unreleased hard white winter experimental lines from Kansas State University. The objective of the cross was to develop a hard white winter wheat variety with herbicide resistance and adaptation to the semiarid area in western Kansas. Clara CL was released because of its tolerance to imazamox herbicide, high grain yield potential under nonirrigated conditions in western Kansas, preharvest sprouting tolerance, and good disease and insect resistance.
Citation: Martin, Terry J., et al. “Registration of ‘Clara CL’ Wheat.” Journal of Plant Registrations, vol. 8, no. 1, 2014, pp. 38–42. Wiley Online Library, doi:10.3198/jpr2013.07.0040crc.
Keywords: Hard white winter wheat; Wheat; Triticum aestivum L.; Clara CL; Agricultural Research Center–Hays